Health promotion of hypertensive and diabetic patients from the problematization of the territory (Research, Society and Development, 2020)
The objective of this study was to describe the mechanisms used by nursing students to promote health and prevent diseases to hypertensive and diabetic patients assisted by a Family Health Strategy team, based on a problematic teaching and learning methodology. This is an experience report of nursing students from the Federal University of Piauí during the course of Curricular Internship I when performing an intervention project in a UBS in the city of Picos-Piauí. It was used to develop the invention project the Problematization Methodology, following the steps proposed by Charles Maguerez. There was a social action of HyperDia, individual consultations and group educational activity, involving more than one hundred patients. The objectives were achieved, making it clear that the importance of nurses is linked to the process of health education, motivating hypertensive and diabetic patients to realize awareness and self-care, knowing the great resistance of adherence to treatment, providing a systematized care with intention. to improve the quality of care, requiring more specific knowledge, planning, organizing and developing with the team individual and collective actions aimed at the promotion, prevention and recovery of the health of these patients.